INSIDEN SYOK DI RUANG TERAPI INTENSIF RSUP PROF. DR. I. G. N. G. NGOERAH DENPASAR - Ambarita, Andini M; Aryabiantara, I Wayan; Dewi, Dewa Ayu Mas Shintya; Hartawan, I Gusti Agung Gede Utara (Essence of Scientific Medical Journal; Vol 22 No 2 (2025): Volume 22 No. 2 (November 2024 - Maret 2025) Essential: Essence of Scientific Medical JournalDO - 10.24843/essential.v22i2.121987, 2025)
ABSTRA CT   Background: Shock is a condition characterized by impaired tissue perfusion, caused by an imbalance between oxygen supply and demand at the cellular level. Method: This study used a descriptive design with samples selected based on inclusion and exclusion criteria. The study was conducted at RSUP Prof. Ngoerah for 6 months using a total sampling technique. Data processing was performed using SPSS ver. 27 with univariate analysis. Results: Secondary data from medical records of patients in the intensive care unit at RSUP Prof. Ngoerah from February to July 2024 showed that a total of 712 at-risk patients were reviewed, with 90 classified as shock cases meeting the inclusion criteria. Discussion: Out of 716 patients, 90 experienced shock, resulting in an incidence rate of 12.57 per 100 patients. Shock incidence by age was as follows: early and late adolescents (5.95 per 100), early and late adults (9.37 per 100), early and late elderly (16.29 per 100), and elderly (15.29 per 100). The incidence was higher in males (13.59 per 100) than females (11.18 per 100). Regarding diagnosis, the shock incidence rate was 11.69 per 100 in non-surgical patients and 13.30 per 100 in surgical patients.  Conclusion: The study found that 12.6% of patients experienced shock, with the highest incidence in the elderly, predominantly male, surgical patients. Septic shock was the most common type.   Keywords: Age, diagnosis, etiology, gender, shock.